PENGARUH PEMBERIAN INSENTIF TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR CAMAT WARA BARAT KOTA PALOPO - Banna , Silpa; Pagallak, Chika; Bernadet, Bernadet; Nelia, Nelia; Amri , Amri (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
This study aims to determine the effect of providing incentives on employee work productivity at the Wara Barat sub-district office, Palopo City. This study uses quantitative and qualitative data sourced from primary data and secondary data with descriptive analysis methods, validity and reliability tests and simple linear regression analysis. The results showed that the incentive variable (X) had an effect on the performance (Y) of employee work productivity at the Wara Barat sub-district office in Palopo City.